Determining the in vivo regulation of cardiac pyruvate dehydrogenase based on label flux from hyperpolarised [1-13C]pyruvate. - Schroeder, M; Atherton, H; Heather, L; Griffin, J; Clarke, K; Radda, G; Tyler, D (2011)
Pyruvate dehydrogenase (PDH) is a key regulator of cardiac substrate selection and is regulated by both pyruvate dehydrogenase kinase (PDK)-mediated phosphorylation and feedback inhibition. The extent to which chronic upregulation of PDK protein levels, acutely increased PDK activity and acute feedback inhibition limit PDH flux remains unclear because existing in vitro assessment methods inherently disrupt the regulation of the enzyme complex. We have demonstrated previously that hyperpolarised (13)C-labelled metabolic tracers coupled with MRS can monitor flux through PDH in vivo. The aim of this study was to determine the relative contributions of acute and chronic changes in PDK and PDH activities to in vivo myocardial PDH flux. We examined both fed and fasted rats with either hyperpolarised [1-(13)C]pyruvate alone or hyperpolarised [1-(13)C]pyruvate co-infused with malate [to modulate mitochondrial nicotinamide adenine dinucleotide (NADH/NAD(+)) and acetyl-coenzyme A (acetyl-CoA)/CoA ratios, which alter both PDH activity and flux]. To confirm the metabolic fate of infused malate, we performed in vitro (1)H NMR spectroscopy on cardiac tissue extracts. We observed that, in fed rats, where PDH activity was high, the presence of malate increased PDH flux by 27%, whereas, in the fasted state, malate infusion had no effect on PDH flux. These observations suggest that pyruvate oxidation is limited by feedback inhibition from acetyl-CoA only when PDH activity is high. Therefore, in the case of PDH, and potentially other enzymes, hyperpolarised (13)C MRI can be used to assess noninvasively enzymatic regulation.